KORELASI WORK AS MEANING TERHADAP QUIET QUITTING PADA PEGAWAI PERUSAHAAN WILAYAH JABODETABEK - Wahyono, Dhamodhara; Irene, Patricia; Tasrief, Rafly Anugrah M; Julian, Welvin; Chandika, Jessica (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
The advancement of technology, the shift to the Industry 5.0 era, and the adoption of Work From Home (WFH) have changed work dynamics, triggered stress, and reduced employee engagement, contributing to the rise of the quiet quitting. This study analyzes the correlation between work as meaning and quiet quitting among 338 employees in Jabodetabek aged 20 to 40 years. Using a quantitative correlational method with questionnaires, the results found a significant negative correlation (rs = -0.322, p<0.000), meaning that higer perceptions of meaningful work are associated with lower tendecies for quiet quitting. Comparative analysis showed that managerial employees scored highest in work as meaning and lowest in quiet quitting, while operational employees showed the opposite trend. These results emphasize the importance of creating meaningful work environments to boost employee engagement and reduce the likelihood of quiet quitting, especially amid rapid technological and workplace changes.